2013
DOI: 10.1021/ie401147u
|View full text |Cite
|
Sign up to set email alerts
|

New Ecological Lubricants on the Basis of Lyotropic Liquid Crystals Formed by Solutions of Maracuja Oil Ethoxylate

Abstract: Aqueous 60% solutions of maracuja oil ethoxylated with 60 mol of ethylene oxide containing hexagonal mesophases were proposed as model biocompatible safe-to-use lubricants. Tests were carried out at steady loads using a four-ball tester (Tester T-02) (1−6 kN) and a ball-on-disk tribometer (Tester T-11) (10−50 N) in order to verify tribological properties of the solutions. At high loads (Tester T-02) a significant, almost 4.5-fold reduction in the coefficients of friction (μ) and about 2.5-fold decrease in wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The search for similar lubricants led the authors of [66] to use aqueous solutions of maracuja oil, ethoxylated with 60 mol of ethylene oxide (MEO 60 ). It was found that when the concentration of this compound in water is about 60%, a fan-shaped texture is formed that is characteristic of the lyotropic hexagonal phase.…”
Section: Ionogenic Lyotropic Mesogensmentioning
confidence: 99%
“…The search for similar lubricants led the authors of [66] to use aqueous solutions of maracuja oil, ethoxylated with 60 mol of ethylene oxide (MEO 60 ). It was found that when the concentration of this compound in water is about 60%, a fan-shaped texture is formed that is characteristic of the lyotropic hexagonal phase.…”
Section: Ionogenic Lyotropic Mesogensmentioning
confidence: 99%
“…Sulek et al have developed a biocompatible aqueous system of passionfruit oil ethoxylate. The low movement resistance and high load-bearing capacity of such systems are the result of the adsorption of a protective layer with ordered structure, which is concluded as an adsorptive-structural mechanism [47]. In addition, they have used biodegradable multi-component solutions based on alkyl polyglycosides (APGs) as a component to reduce friction and wear [48,49].…”
Section: Introductionmentioning
confidence: 99%